Seat Belt Use among Car Users in Malaysia. - Subramaniam, Kulanthayan; Abdul Rahim, Raha; Law, Teik Hua; Radin Sohadi, Radin Umar (2004)
The car is the second (40%) most common mode of transportation in Malaysia. In terms of fatal road accidents, car drivers constitute about 9.0% and passengers 13.6% of fatalities. The major cause of car accupants’ fatality in such accidents is head injuries, which consist of more than half (56.4%) of the fatalities. Thus restraining the head and body, the initial position is the most important injury control strategy for car users. The use of seat belts was deemed one of the most effective ways to reduce road accident fatalities in Malaysia and consequently the mandatory seat belt law was enforced in the early seventies. Therefore, a study on factors influencing the compliance behaviour of seat belt use among cars is needed as to date no such research has been undertaken in Malaysia. A questionnaire study was carried out in Selangor, Malaysia on the compliance behaviour of car occupants in relation to seat belt use. A total of 237 respondents were interviewed and the data analysed using logistic regression method. Six variables were found to be significant at 5 percent level (p<0.05): seating position, location of travel, education level, speeding, night-time driving and enforcement. Compliance with the seat belt law was higher among drivers, educated car users, in the presence of enforcement activities, traveling in city-center areas and car users with a positive attitude towards the risks of speeding and night driving.